2003
DOI: 10.1002/cne.10839
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic changes in the expression of delta opioid receptors in spinal cord and dorsal root ganglia

Abstract: To assess the validity of rodent models for investigating the role of delta opioid receptors (DOR) in analgesia, the distribution of DOR binding and mRNA were compared between rodent and primate spinal cord and dorsal root ganglia (DRG), using receptor autoradiography and in situ hybridization, respectively. In mouse and rat spinal cord, [(125)I]-deltorphin-labeled DOR binding sites were detected throughout the gray matter. In contrast, in primate and particularly in human spinal cord, DOR binding was mainly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
85
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 50 publications
16
85
0
1
Order By: Relevance
“…Double immunofluorescence staining showed that DORs were present in SP-and CGRP-positive LDCVs in small DRG neurons in mice ( Figure 2A and Supplementary information, Figure S2A). This immunostaining pattern, which was shown with antibodies against DOR1 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] , was abolished by the deletion of Oprd1 exon 1 in mice (Supplementary information, Figure S2A). Furthermore, β2 AR, G αi2 , PLCβ2, VGCC α2δ1 and P2X purinoceptor 2 (P2X 2 ) were present in SP-positive LDCVs in small DRG neurons (Figure 2A).…”
Section: Ldcv Localization Of Gpcrs Signaling Molecules and Ion Chanmentioning
confidence: 78%
See 1 more Smart Citation
“…Double immunofluorescence staining showed that DORs were present in SP-and CGRP-positive LDCVs in small DRG neurons in mice ( Figure 2A and Supplementary information, Figure S2A). This immunostaining pattern, which was shown with antibodies against DOR1 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] , was abolished by the deletion of Oprd1 exon 1 in mice (Supplementary information, Figure S2A). Furthermore, β2 AR, G αi2 , PLCβ2, VGCC α2δ1 and P2X purinoceptor 2 (P2X 2 ) were present in SP-positive LDCVs in small DRG neurons (Figure 2A).…”
Section: Ldcv Localization Of Gpcrs Signaling Molecules and Ion Chanmentioning
confidence: 78%
“…After three PBS washes, cells were labeled with the primary antibodies. We used antibodies against DOR1 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] (1:30 000; DiaSorin), G αi2 (1:100; Santa Cruz), G β1 (1:200; Santa Cruz), G γ5 (1:400; Santa Cruz), PLCβ2 (1:200; Santa Cruz), P2X 2 (1:1 000; Chemicon), Fzd8 (1:400; Everest Biotech), β1 AR (1:400; Santa Cruz), β2 AR (1:200; Santa Cruz), SP (1:500; Neuromics), CGRP (1:500; Biogenesis), Dvl1 (1:200; a gift from Dr. Zhen-Ge Luo), VGCC α2δ1 (1:100; Affinity BioReagents) and Myc (1:500; a gift from Dr Jin-Qiu Zhou).…”
Section: Immunostainingmentioning
confidence: 99%
“…Therefore, the antiserum primarily recognizes DOR1, although an excessive amount of antiserum might generate nonspecific binding. Using the antibodies above at a dilution of 1:30,000, we found that DORs were present in peptidergic and vanilloid receptor type 1-ir small neurons ( Interestingly, we found the presence of DORs on the cell surface in ∼14% of DRG neurons when we tested another antibody, now against DOR1 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] (1:60,000-120,000; Alomone) that also recognized Myc-DOR1 expressed in HEK293 cells ( Fig. 3 H and I and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DOR1 mRNA has been found in many DRG neurons, including large ones, and at lower levels in both isolectin B4-negative (IB4 − , peptidergic) and IB4-positive (IB4 + ) subsets of small neurons (10)(11)(12). In neurons of the painmodulating system, intracellular DORs are inserted into the plasma membrane following a variety of chemical and behavioral stimuli, including sustained pain conditions and chronic opioids (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
See 1 more Smart Citation